“A morte pede passagem” : uma análise do princípio da precaução, das dimensões da sustentabilidade e a relação com os organismos geneticamente modificados. (2019)
The objective of this article is to analyze the reality of the application of the precautionary law and current legislation on GMOs, as well as to analyze how planting and consumption of GM foods can affect sustainability. An inductive method with reference, category or operational techniques, as well as literature review was used in the methodology. It is concluded that it seems that GMO directly affects the three dimensions of sustainability: the environment due to the impacts caused to the environment; the social impact of the impact on the health of the population and the economy that, before prioritizing profits on the use of a production, should have less impact on the environment and in the life of people.